Rancang Bangun Sistem Pembayaran SPP Berbasis Web dengan Metode Waterfall pada SMK Swasta Parulian 2 Medan - Elisabet Ndruru; Cut Try Utari; Taufik Ismail Simanjuntak (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
Information technology is used in the data processing process which includes processing, obtaining data, compiling data, storing data and manipulating data in various ways so as to present qulity information, namely information that is accurate, relevant and timely. One example of a field that has benefit greatly from the development of science and information technology is the field of education. There are quite a lot of benefits from using information and communication technology in the word of education, both for teaching and learning purposesand for school administration management purposes. Website based school administration payment information system to provide effective and efficient solutions to overcome school payment management problems. This research aims to build applications for students and financial departemens in the digital payment process at school. By using this applications, it is hoped that the tuition payment process can be carried out quickly, accurately and safely. The research method applied in this thesis is to use the waterfall method, which is software development that uses sequential and systematic stages, such as a waterfall flowing from top to buttom. The conclusion is that admin (administration), school principals, and students can log in to the website using their respective usernames and passwords provided by the admin.